100 questions & answers about lung cancer 2026-02-16T01:22:48+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Schiller, J. H. (Joan H.), 1954- .); Cipau, Amy; Parles, Karen (100 questions & answers, 2010)

(untitled)
Overview: EMPOWER YOURSELF! No one with lung cancer needs to be alone in their fight against this disease. 100 Questions & Answers About Lung Cancer, Second Edition, enables patients and their families to seek out the best treatment possible for early detection of lung cancer. Providing both the doctor's and patient's point of view, this book is a complete guide to understanding treatment options, post-treatment quality of life, sources of support, and much more. Through 100 Questions & Answers About Lung Cancer, Second Edition, expert authors use their experiences with patients to provide support and hope to the tens of thousands of people coping with lung cancer